REPRESENTASI TINDAKAN DIKRIMINASI RAS KULIT HITAM DALAM FILM GLORY ROAD - Prayuda, Ngakan Bayu; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2018)
ABSTRA CT   Discrimination is the distinction between unfair and unbalanced treatment carried out to distinguish between individuals, or groups based on specific attributes such as race, ethnicity, religion, or social class membership. The Glory Road film tells of a team that changes everything in national basketball rules and black players have never been on the national players list, because they consider black players unable to lead, and moreover it's difficult to hold back emotions. This study includes qualitative research that focuses on the analysis of semiotics developed by Roland Barthes which consists of denotation, connotation and myth. The purpose x of this study was to x find out the representation of black racial discrimination in r the film Glory Road. Based on the analysis of related scenes by using Roland Barthes' semiotics method in the film, addressing direct and indirect discrimination. The results were shown by the black race being underestimated by statements from the white race. Not only that, the black race while on the field was seen to be treated differently when on the field or harm the black race. This is displayed through various scenes in the film. Keywords: Discrimination,Representation,Semiotics, Film